1996
DOI: 10.1111/j.1365-2621.1996.tb13180.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Recovered Neck Bone Lean and Ascorbic Acid Improve Color Stability of Ground Beef Patties

Abstract: Ground beef patties at two ascorbic acid (Asc) levels (0 and 1,000 ppm) and three mechanically recovered neck bone lean (MRNL) levels (0, 15 and 30%) were analyzed for percentage surface metmyoglobin (metMb) and HunterLab L* and a* values over 6 days of retail display. Data were collected for two replications. Patties made with Asc had less (P Ͻ 0.01) surface metMb than patties made without Asc on days 1-4 of retail display. Ascorbic acid and MRNL acted synergistically to improve surface color. Patties made wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Since the mechanically recovered product also had a higher pH they felt that it is logical for mechanically recovered meat to remain red longer. Their unique finding was that ascorbic acid also acts synergistically with mechanically recovered meat which contains marrow to increase color stability of beef patties (Demos et al, 1996).…”
Section: Resultsmentioning
confidence: 98%
“…Since the mechanically recovered product also had a higher pH they felt that it is logical for mechanically recovered meat to remain red longer. Their unique finding was that ascorbic acid also acts synergistically with mechanically recovered meat which contains marrow to increase color stability of beef patties (Demos et al, 1996).…”
Section: Resultsmentioning
confidence: 98%
“…Kamarei et al, (1979) reported the generation of free radicals during food processing and storage and upon irradiation the free binding site of myoglobin reacts with such free radicals to form the brown colored metmyoglobin (Giroux et al, 2001). In this respect, consumers consider the visual appearance to be one of the major parameters to judge the quality and acceptability of meat (Demos et al, 1996 andZhao et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The samples were packed in low density polyethylene wrap (Oxygen transmission rate: 35,273 cc /m 2 ·24 h·atm, 0.01 mm thickness, 3M Co, Korea) for measurement. The reflectance was measured at 473, 525, 572, and 730 nm using a UV spectrometer (UV-240 1PC, Shimadzu Corp, Kyoto, Japan) and the percentage (%) of MetMb was calculated according to the method of Demos et al [ 19 ]. R630 and R580, an indicator of red intensity by OxyMb, was calculated as the reflectance difference at 630 nm and 580 nm; DeoxyMb was calculated as 100 minus OxyMb and MetMb.…”
Section: Methodsmentioning
confidence: 99%